2010
DOI: 10.19030/ajbe.v3i2.392
|View full text |Cite
|
Sign up to set email alerts
|

Online And Paper Course Evaluations

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…report that online means were "marginally lower" (p. 50) (1.6% lower) than those for paper evaluations, but that the difference is "of little practical significance" (p. 50). Similarly, Guder and Malliaris (2010) found "slight drops" (p. 136) in online scores, but these could have been due to "random fluctuations" and, anyway, were slight (p. 136).…”
Section: Claimed Advantagesmentioning
confidence: 88%
See 1 more Smart Citation
“…report that online means were "marginally lower" (p. 50) (1.6% lower) than those for paper evaluations, but that the difference is "of little practical significance" (p. 50). Similarly, Guder and Malliaris (2010) found "slight drops" (p. 136) in online scores, but these could have been due to "random fluctuations" and, anyway, were slight (p. 136).…”
Section: Claimed Advantagesmentioning
confidence: 88%
“…Grade expectation is also reported by , Isely and Singh (2005), and to influence evaluation scores. , Guder and Malliaris (2010), , and Robinson, White, and Denman (2004) suggest that faculty support for online evaluations and the actual effort that they put into supporting it (e.g., discussing it in class, showing students how to access the software, indicating the importance of student feedback, sending emails to remind students to complete), exert an influence on response rates. suggests that differences found are not due to whether the evaluations are conducted on paper or online, but to the environment, types of student, and whether or not the classes are on campus.…”
Section: Claimed Advantagesmentioning
confidence: 99%
“…Also, students who completed the online version provided more and lengthier comments. 35 A third, smaller study found no statistical difference between mean scores on course evaluations delivered online even though there was a higher response rate for paper evaluations. 34 What these study results consistently suggest is that online evaluations are a suitable alternative for conducting evaluations as scoring patterns are similar even if response rates are lower than with paper evaluations.…”
Section: Administering Student Ratings Of Instructionmentioning
confidence: 89%
“…However, analysis of the results showed that there was no significant difference in the paper and online values given to courses or faculty for whom evaluations existed in both paper and online formats (Guder et al, 2009). However, with the online evaluations, the response rate dropped by 26% on the undergraduate level (Guder & Malliaris, 2010). Given this significant drop, we were interested in not only the comparison of values with the previous years, but also why the drop might have occurred.…”
Section: Introductionmentioning
confidence: 99%